Municipal bonds: A viable funding option for Oradea Local Public Administration (Romania) - Liliana Bunescu (Colegio de Economistas de A Coru\~na, 2010)
In a market economy government resources are often insufficient to cover all the public budget needs. Public capital collecting process presents a particular interest considering the need of getting them with lower costs. The options for collecting public resources are characterized by diversity and complexity. One of them is based on municipal bonds funds. This paper explores the potential of public bonds issued at a local level in raising capital for infrastructure investments in Romanian public administration. This paper is not meant to be an empirical study at national level because sub-sovereign bonds market in Romania is not very developed. This paper is limited to a case study of public financing methods for a Romanian local public administration. Local authorities from Oradea have no other possibility without one of borrowing to achieve the objectives proposed. Thus, it resorted to a set of internal and external loans. Our study contents a comparative cost analysis of public financing by loans. The analysis lead to the result that the cheapest source of financing is the loan offered by the European Investment Bank, followed by municipal bonds issuing.
Keywords: H74; 330